PERSPEKTIF GENDER DALAM PEMBELAJARAN MATEMATIKA - Zubaidah Amir MZ (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
Math is taughtwith the aimto prepare students to be able to usemathematics andmathematicalmindset in everyday life. In studying mathematics,many students bothmen and women considermathematics as a boring subject. Based on this, the gender aspect in learning mathematics become educators concern. Gender differences not only result in differences in mathematical ability, but also a way of gaining knowledge of mathematics. Some of the notion that women are not quite managed to learn math than men. In addition, women almost never have a thorough interest in theoretical questions such as the male. Women are more interested in practical matters than the theoretical. But on the other hand, not a few female students who have success in math skills. Writing this article aims to analyze some of the results of research on gender differences in mathematics learning. The methodology used is a literature study. This study found evidence of differences in the strategies used boys and girls, even to solve the spatial.